Integration of Computed Tomographic Angiography Spot Sign and Noncontrast Computed Tomographic Hypodensities to Predict Hematoma Expansion - Morotti, Andrea; Boulouis, Gregoire; Charidimou, Andreas; Schwab, Kristin; Kourkoulis, Christina; Anderson, Christopher D.; Gurol, M. Edip; Viswanathan, Anand; Romero, Javier M.; Greenberg, Steven M.; Rosand, Jonathan; Goldstein, Joshua N. (Stroke (1970), 2018)
BACKGROUND AND PURPOSE—Noncontrast computed tomographic (CT) hypodensities represent an alternative to the CT angiography spot sign (SS) to predict intracerebral hemorrhage (ICH) expansion. However, previous studies suggested that these markers predicted hematoma expansion independently from each other. We investigated whether the integration of SS and hypodensity (HD) improved the stratification of ICH expansion risk. METHODS—A single-center cohort of consecutive patients with ICH was retrospectively analyzed. Patients with available CT angiography, baseline, and follow-up noncontrast CT images available were included. Trained readers reviewed all the images for SS and HD presence, and the study population was classified into 4 groupsSS and HD negative (SS−HD−), SS positive only (SS+HD−), HD positive only (SS−HD+), and SS and HD positive (SS+HD+). ICH expansion was defined as hematoma growth >33% or >6 mL. The association between SS and HD presence and ICH expansion was investigated with multivariable logistic regression. RESULTS—A total of 745 subjects qualified for the analysis (median age, 73 years; 54.1% men). The rates of ICH expansion were 9.3% in SS−HD−, 25.8% in SS+HD−, 27.4% in SS−HD+, and 55.6% in SS+HD+ patients (P<0.001). After adjustment for potential confounders and keeping SS−HD− subjects as reference, the risk of ICH expansion was increased in SS+HD− and SS−HD+ patients (odds ratio, 2.93, P=0.002 and odds ratio, 3.02, P<0.001, respectively). SS+HD+ subjects had the highest risk of hematoma growth (odds ratio, 9.50; P<0.001). CONCLUSIONS—Integration of SS and HD improves the stratification of hematoma growth risk and may help the selection of patients with ICH for antiexpansion treatment in clinical trials.